Dystocia Caused by Bilateral Muscular Hypertrophy and its Surgical Management in Murrah Buffalo - Yadav, Brijesh Kumar; Arya, Manish; Jayaramudu, Yerukala; Kumar, Brijesh; Khan, Meraj Haider (The Indian Journal of Animal Reproduction, 2025)
A pluriparous Murrah buffalo with a history of dystocia and full gestation was brought to the Referral Veterinary  Polyclinic ICAR-IVRI Izatnagar Bareilly. Repulsion and force traction applied to deliver the fetus were not successful in  relieving dystocia. Given that the case was not fresh and that additional manipulative treatments had been performed at  the field level, the decision was made to deliver the fetus via caesarean section. Muscular hypertrophy of the fetal neck  and shoulder region was identified as the cause of the dystocia, which was effectively treated with a Caesarean section.
Keywords: Dystocia; Bilateral Muscular hypertrophy; buffalo; Caesarean section